OTX008, a selective small-molecule inhibitor of galectin-1, downregulates cancer cell proliferation, invasion and tumour angiogenesis - Astorgues Xerri, Lucile (2014)
Background Galectin-1 (Gal1), a carbohydrate-binding protein is implicated in cancer cell proliferation, invasion and tumour angiogenesis. Several Gal1-targeting compounds have recently emerged. OTX008 is a calixarene derivative designed to bind the Gal1 amphipathic β-sheet conformation. Our study contributes to the current understanding of the role of Gal1 in cancer progression, providing mechanistic insights into the anti-tumoural activity of a novel small molecule Gal1-inhibitor. Methods We evaluated in vitro OTX008 effects in a panel of human cancer cell lines. For in vivo studies, an ovarian xenograft model was employed to analyse the antitumour activity. Finally, combination studies were performed to analyse potential synergistic effects of OTX008. Results In cultured cancer cells, OTX008 inhibited proliferation and invasion at micromolar concentrations. Antiproliferative effects correlated with Gal1 expression across a large panel of cell lines. Furthermore, cell lines expressing epithelial differentiation markers were more sensitive than mesenchymal cells to OTX008. In SQ20B and A2780-1A9 cells, OTX008 inhibited Gal1 expression and ERK1/2 and AKT-dependent survival pathways, and induced G2/M cell cycle arrest through CDK1. OTX008 enhanced the antiproliferative effects of Semaphorin-3A (Sema3A) in SQ20B cells and reversed invasion induced by exogenous Gal1. In vivo, OTX008 inhibited growth of A2780-1A9 xenografts. OTX008 treatment was associated with downregulation of Gal1 and Ki67 in treated tumours, as well as decreased microvessel density and VEGFR2 expression. Finally, combination studies showed OTX008 synergy with several cytotoxic and targeted therapies, principally when OTX008 was administered first. Conclusion This study provides insights into the role of Gal1 in cancer progression as well as OTX008 mechanism of action, and supports its further development as an anticancer agent.